2017
DOI: 10.1093/jac/dkx168
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of azole-resistant Aspergillus fumigatus from the environment in the south-eastern USA

Abstract: These findings suggest the development of resistance to azole antifungals in A. fumigatus may be present where agricultural azoles are used in the USA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 29 publications
0
63
1
4
Order By: Relevance
“…As a result, resistant isolates likely persist alongside wild-type isolates in the environment (the frequency with which this happens in the United States is unknown). We recently identified azole-resistant A. fumigatus containing the TR 34 mutation in an experimental peanut field in Georgia that had been treated with azole fungicides (18). In the present study, Georgia contributed more clinical isolates to our survey than any other state, but we did not observe the TR 34 mutation from any of these isolates.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…As a result, resistant isolates likely persist alongside wild-type isolates in the environment (the frequency with which this happens in the United States is unknown). We recently identified azole-resistant A. fumigatus containing the TR 34 mutation in an experimental peanut field in Georgia that had been treated with azole fungicides (18). In the present study, Georgia contributed more clinical isolates to our survey than any other state, but we did not observe the TR 34 mutation from any of these isolates.…”
contrasting
confidence: 57%
“…DNA sequence analysis of the CYP51A gene was performed for any isolate with elevated MICs confirmed via broth microdilution, as previously described (18). Sequencing revealed that 14 of 20 isolates contained an amino acid substitution in Cyp51A (Table 1).…”
mentioning
confidence: 99%
“…The samples were processed as described previously by Snelder et al 9 and Hurst et al 16 with some modifications. Briefly, 2 g of soil was suspended in 15 ml of sterile 0.1 M sodium pyrophosphate.…”
Section: Methodsmentioning
confidence: 99%
“…In the Unites States (U.S.), azole-resistant A. fumigatus strains with TR 34 /L98H and TR 46 /Y121F/T289A alleles have been recently reported in patients 14,15 . Additionally, azole-resistant A. fumigatus isolates with TR 34 /L98H alleles were detected in a peanut field in Georgia 16 . Otherwise, very little information about the frequency of azole-resistant A. fumigatus in agricultural settings in the U.S. is available.…”
Section: Mainmentioning
confidence: 97%
“…A. fumigatus also produces the mycotoxin gliotoxin (GLI) (Kupfahl et al 2008). Indeed, in Manchester, UK, azole-resistant strains were first detected in 1999 (Howard et al 2009) and are now commonly found in Switzerland, USA, India and China (Hurst et al 2017;Lockhart et al 2011;Riat et al 2018). However, at the present time, no regulations exist with regard to GLI exposure.…”
Section: Introductionmentioning
confidence: 99%